Penerapan Metode Pembelajaran Outing Class Dalam Meningkatkan Kecerdasan Naturalis Siswa Kelas III SD Negeri 0104 Sibuhuan - Rhamdan; Yuli Marlina; Era Mutiah (Journal Education Innovation (JEI), 2025)
Based on the research results, it can be concluded that: (1) The natural intelligence of grade III students of SD Negeri 0104 Sibuhuan in the pre-cycle was only 2 students or 9.52% with “very good” natural intelligence, 4 students or 19.05% with “good” natural intelligence, 6 students or 28.57% with “sufficient” natural intelligence, 8 students or 38.10% with “less” natural intelligence and 1 student or 4.76% with “very less” natural intelligence. (2) The application of the outing class learning method in improving the natural intelligence of grade III students of SD Negeri 0104 Sibuhuan in cycle I was 6 students or 28.57% with “very good” natural intelligence, 8 students or 38.10% with “good” natural intelligence, 7 students or 33.33% with “sufficient” natural intelligence, no “less” natural intelligence and no “very less” natural intelligence. In cycle II, there were 14 students or 66.67% with "very good" naturalist intelligence, 7 students or 33.33% with "good" naturalist intelligence, no students with "sufficient" naturalist intelligence, no "less" naturalist intelligence and no "very less" naturalist intelligence, so it can be concluded that by implementing the outing class learning method, it can improve the naturalist intelligence of grade III students of SD Negeri 0104 Sibuhuan.